1264 Community-based farm safety intervention in south korea. (24th April 2018) - Kim, K; Choi, D; Chae, H; Kim, H; Kim, K; Lee, K
Abstract : Introduction: Intervention strategies to reduce agricultural injuries for self-employed farmers have been sought and evaluated in many prior studies. The aim of this study is to introduce the characteristics and effects of several types of farm safety interventions in South Korea. Methods: This study reviewed reports and documents of community-based farm safety interventions conducted by Korean central government through RDA (Rural Development Administration). The frameworks, main contents, effects, and implications of the intervention programs were described. Results: Since 2006, three main community-based farm safety intervention programs have been conducted by RDA, which were 'Farm Safety Model (2006–2015, 133 farm villages)', 'Supporting Program of Farming Convenient Equipment (2008–2017, 1484 farm villages)', and 'Customised Farm safety Management Program (2015~current, 230 farmer's cooperative units in 2015)'. 'Farm Safety Model' where professionals facilitated various interventions including farm safety education, an evaluation of risk factors on farm worksites, and health examination were apprised as effective in enhancing safety consciousness and safety management capacity of farmers. 'Supporting Program of Farming Convenient Equipment' was proved to reduce symptoms of musculoskeletal disorders among farmers participated. 'Customised Farm safety Management Program' that consisted of safety education, evaluation of risk factors on farm worksites, and customised supporting for occupational health and safety was evaluated as effective in enhancing the level of safety management on farming environment and hazards. Conclusion: Based on experiences from the existing intervention programs, the following are recommended for future strategies for agricultural health and safety: the main stream of community-based interventions is better to be farmers or farm leaders; intervention programs are recommended to contain both safety education/training and working environment interventions at least; national training programs and system for farm safety managers and farm leaders are needed. Funding: Rural Development Administration, Republic of Korea (Project No. PJ01250905).